![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: 3(2x-1)=-2x+3) - 3(2x-1)=-2(x+3) - find the term independent of x in the expansion of (3/2x^2-1/3x)^6 - 1/2x+1/3y=2 and 1/3 x+1/2y=13/6 - 2x+y+z=1 x-2y-z=3/2 3y-5z=9 - 3/4(7x-1)-(2x-1-x/2)=x+3/2 - if x+1 is a factor of 2x^3+ax^2+2bx+1 and 2a-3b=4 - find the asymptotes of the curve x^(3)+2x^(2)y-xy^(2)-2y^(3)+xy-y^(2)-1=0 - solve the system of equations x+2y+3z=1 2x+3y+8z=2 x+y+z=3 - u=cosec^(-1)((x^((1)/(2y^((1)/(2x^((1)/(3))+y^((1)/(3))))^(1/2) - solve for x 2(2x-1/x+3)-3x+3/2x-1)=5 - find asymptotes of the curve x^3+2x^2y-xy^2-2y^3+xy-y^2=1 - x-2/4+1/3=x-2x-1/3 - find the remainder when p(x)=x^3-6x^2+14x-3 when divided by 1-2x - 3(2x 1)= 2(x+3) Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.